Self-Awareness Analysis of Archery Accuracy 30 Meter Distance at Muara Bungo Ksatria Archery Club - Aryani, Fara Dila Dwi; Hendra, Jhony; Wulandari, Titis (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Archery is a sport that uses a bow and arrow to shoot a target. The purpose of this study was to determine the self-awareness of the accuracy of the 30-meter distance of the Ksatria Archery Club. This study uses a descriptive qualitative approach methodology. Descriptive qualitative research is research that needs to be done based on a problem that is studied quantitatively, but the solution has not been revealed. In this study, the researcher used a descriptive quantitative research type. The sampling technique used purposive sampling totaling 10 standard bow athletes with data collection techniques, namely providing questionnaires and interviews. Based on the results of research on self-awareness of 30-meter archery accuracy at the Muara Bungo Archery Knights Club, it shows that the athletes' self-awareness is in the Good category with an average percentage of 84.95%.